Trends in seroprevalence of SARS‐CoV‐2 and infection fatality rate in the Norwegian population through the first year of the COVID‐19 pandemic. Issue 2 (9th November 2021) - Tunheim, Gro; Rø, Gunnar Øyvind Isaksson; Tran, Trung; Kran, Anne‐Marte Bakken; Andersen, Jan Terje; Vaage, Eline Benno; Kolderup, Anette; Vaage, John Torgils; Lund‐Johansen, Fridtjof; Hungnes, Olav
Abstract: Background: Infection with the novel coronavirus SARS‐CoV‐2 induces antibodies that can be used as a proxy for COVID‐19. We present a repeated nationwide cross‐sectional study assessing the seroprevalence of SARS‐CoV‐2, the infection fatality rate (IFR), and infection hospitalization rate (IHR) during the first year of the pandemic in Norway. Methods: Residual serum samples were solicited in April/May 2020 (Round 1), in July/August 2020 (Round 2) and in January 2021 (Round 3). Antibodies against SARS‐CoV‐2 were measured using a flow cytometer‐based assay. Aggregate data on confirmed cases, COVID‐19‐associated deaths and hospitalizations were obtained from the Emergency preparedness registry for COVID‐19 (Beredt C19), and the seroprevalence estimates were used to estimate IFR and IHR. Results: Antibodies against SARS‐CoV‐2 were measured in 4840 samples. The estimated seroprevalence increased from 0.8% (95% credible interval [CrI] 0.4%–1.3%) after the first wave of the pandemic (Rounds 1 and 2 combined) to 3.2% (95% CrI 2.3%–4.2%) (Round 3). The IFR and IHR were higher in the first wave than in the second wave and increased with age. The IFR was 0.2% (95% CrI 0.1%–0.3%), and IHR was 0.9% (95% CrI 0.6%–1.5%) for the second wave. Conclusions: The seroprevalence estimates show a cumulative increase of SARS‐CoV‐2 infections over time in the Norwegian population and suggest some under‐recording of confirmed cases. The IFR and IHR were low, corresponding to the relatively low number of COVID‐19‐associated deaths and hospitalizations in Norway. Most of the Norwegian population was still susceptible to SARS‐CoV‐2 infection after the first year of the pandemic.